Aplicação da entropia de permutação A sinais EEG durante estimulação dinâmica de cenário virtual - Liquori, Danielle Martins da Silva (2017)
Adjustments in the integration of sensory information, which occur in the cortex due to disturbances in postural control, cause an increase in the activity of the cortex, and this increased activity generates the desynchronism in the EEG. In this study, such changes were caused by a dynamic visual stimulus (ED). One form of EEG signal analysis is the calculation of signal entropy, which measures the degree of complexity about a particular message or signal. This study consisted in the use of Permutation Entropy (PE) for the analysis of the EEG records obtained during ED with the individual in the orthostatic and seated positions. The results showed a variation in EEG signal complexity, elicited by dynamic visual stimulation in the occipital, parietal and central leads, but not in the frontal ones, in the frequency range between 1 and 40 Hz. The analysis performed in the beta1 neural rhythm indicated a change in the Complexity of this rhythm, but only on leads O1 and O2. Theta, alpha and beta2 rhythms presented significant variation in the occipital, parietal and central derivations; again the frontal leads did not present a variation of complexity. The gamma rhythm showed no variation in any derivation. The analysis of the stabilometric signals indicated that there is variation of the entropy values when these signals correspond to the anteroposterior direction of the individuals' balance during the movement of the ED.